EVOLUTION, TRANSFORMATION AND BIOLOGICAL ACTIVITY - et al., Lazizakhon Akramovna Gafurova (International Journal of Advanced Science and Technology, 2019)
The features of morphogenetic characteristics, degree of gypsation and salinization, humus state, total chemical composition, time history (over the years) of gray-brown, desert-meadow, meadow-alluvial, marsh-meadow soils of the territory are considered in the paper; the formation of a new genetic group of soils as a result of ecological-genetic aspects, transformation and evolutionary changes in the soil processes occurring under anthropogenic factors are determined; the formation of prairiefication processes as a result of soil transition from the automorphic to the semi-hydromorphic and hydromorphic regimes under the influence of the Tuyamuyun reservoir is determined; soil fertility of the territory is estimated according to their current state and properties; soil and         soil-assessment maps, as well as the maps of crops distribution are developed. Determination of the influence of gypsum content and degree of salinization on enzymatic activity (catalase, peroxidase, polyphenol oxidase) and “soil respiration”, as well as on their alterations over the seasons of year; indicators of biological activity (BA), total relative biological activity (TBA) of soils, indicators on soil degradation have been developed. The aim of research is to determine the current state of the Tashsaka Plateau soils, their evolution and climatic conditions, fertility assessment and the development of measures aimed at distribution of agricultural crops, is a comprehensive study of the seasonal dynamics of the basic properties and biological activity of gypsum soils, development of criteria for the indicator of their degradation. The objects of study are the virgin and irrigated gray-brown, gray-brown-meadow, desert-meadow, meadow and marsh-meadow soils spread in the Tashsaka Plateau and adjacent territories of the Khazarasp region of Khorezm district, are gypsiferous and saline gray soils, meadow- gray soils, gray soils -meadow, meadow, meadow-marsh soils, as well as salt marshes soils, common in Zarbdar district of Jizzakh region.